2018
DOI: 10.33064/iycuaa201873136
|View full text |Cite
|
Sign up to set email alerts
|

Especies nativas de Trichoderma spp. y su actividad antagónica contra Meloidogyne incognita en Solanum lycopersicum L.

Abstract: En condiciones protegidas, se evaluó el potencial antagónico de cinco especies nativas de Trichoderma; T. harzianum (Th02-04), T. harzianum (Th10-D86), T. simmonsi (Th33-58), T. virens (Th33-59) y T. virens  (Th26-52), especies comerciales y un testigo sin inoculantes fúngicos, distribuidas en un diseño completamente al azar y cuatro repeticiones en plántulas de tomate (Solanum lycopersicum L.), inoculadas con tres aplicaciones de 1 x106 conidias ml-1. Se inocularon 18, 500 huevos de M. incognita y 10 ml con l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
0
0
3
Order By: Relevance
“…At the end of 68 d, all treatments achieved a reduction of females greater than 80 % compared to the control, where the best result was Oxamyl with 92.47 %, although among the two strains evaluated, T. erinaceum was the best performer with 86.74 % (Figure 2). Applications with T. harzianum and T. virens also achieved a decrease in the number of M. incognita females in tomato crops, with a percentage higher than 80 % (Pinzón-Espinoza et al, 2015;Cetz-Chi et al, 2018). Medeiros et al (2017) reported that T. atroviride is able to activate a defense system in response to the attack of M. javanica on tomato plants, where the number of adults and galls was significantly reduced, even without establishing direct contact with the nematode.…”
Section: Number Of M Incognita Femalesmentioning
confidence: 99%
“…At the end of 68 d, all treatments achieved a reduction of females greater than 80 % compared to the control, where the best result was Oxamyl with 92.47 %, although among the two strains evaluated, T. erinaceum was the best performer with 86.74 % (Figure 2). Applications with T. harzianum and T. virens also achieved a decrease in the number of M. incognita females in tomato crops, with a percentage higher than 80 % (Pinzón-Espinoza et al, 2015;Cetz-Chi et al, 2018). Medeiros et al (2017) reported that T. atroviride is able to activate a defense system in response to the attack of M. javanica on tomato plants, where the number of adults and galls was significantly reduced, even without establishing direct contact with the nematode.…”
Section: Number Of M Incognita Femalesmentioning
confidence: 99%
“…Este resultado fue estadísticamente igual al tratamiento 1x10 7 conidios mL -1 (Cuadro 2). Cetz-Chi et al (2018) reportaron incrementos en el crecimiento de plantas de jitomate, con ganancias de altura entre 4.4 y 14.2 % cuando se inocularon con especies nativas: T. virens (Th33-59 y Th26-52) y T. simmonsi (Th33-58), Th33-59 de T. virens incrementó el volumen radical y el peso seco de raíz con respecto al testigo. Ruiz-Cisneros et al (2018) observaron incrementos en altura de planta, diámetro de tallo y longitud de raíz en plantas de jitomate cuando se inocularon con T. asperellum, T. harzianum y T. longibrachiatum en concentraciones de 10 6 conidios mL -1 .…”
Section: Online Publication January 2023unclassified
“…Por ejemplo, T. harzianum contribuyó a una mejor protección de plantas de cacahuate contra la infección de Sclerotium rolfsii en comparación con un fungicida (Michel-Aceves et al, 2013). Por otro lado, T. virens contribuyó a reducir la formación de agallas, el número de huevos y hembras del nematodo fitopatógeno Meloidogyne incognita en Solanum lycopersicum (Chi et al, 2018). Adicionalmente, se demostró el potencial biológico de T. asperellum para controlar el desarrollo de antracnosis ocasionada por Colletotrichum gloeosporioides en frutos de mango (Santos-Villalobos et al, 2013).…”
Section: Importancia Agrícolaunclassified